Proceedings of SPE Annual Technical Conference and Exhibition 2003
DOI: 10.2523/84488-ms
|View full text |Cite
|
Sign up to set email alerts
|

Improved Microseismic Fracture Mapping Using Perforation Timing Measurements for Velocity Calibration

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractA method is decribed where microseismic mapping of hydraulic fractures is improved by using crosswell data to calibrate and/or verify dipole-sonic velocity data. The microseismic technique uses an array of advanced tri-axial receivers to detect microearthquakes induced by a fracture and, thus, provides a real-time image of the fracture and the way it propagates. To apply this technique, the orientation of the receivers must be determined by detecting perforat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 6 publications
0
28
0
Order By: Relevance
“…• Other recommendations such as a matched filter technique to enhance signal from induced microseismic (Hulsey et al, 2009), using perforation timing measurements for velocity calibration (Warpinski et al, 2003), and using source parameters technique to better describe the fracturing process by determining the actual failure mechanism (Mayerhofer et al, 2000) are also suggested for further review. …”
Section: Recommendations and Future Workmentioning
confidence: 99%
“…• Other recommendations such as a matched filter technique to enhance signal from induced microseismic (Hulsey et al, 2009), using perforation timing measurements for velocity calibration (Warpinski et al, 2003), and using source parameters technique to better describe the fracturing process by determining the actual failure mechanism (Mayerhofer et al, 2000) are also suggested for further review. …”
Section: Recommendations and Future Workmentioning
confidence: 99%
“…The origin time of perforation shot was assumed to be known in their study. However, the origin time of perforation shot is difficult to measure accurately [3]. To reduce the effect of the origin time of perforation shot, we develop a novel objective function for VFSA which consists of the travel time differences of P-wave first arrivals between seismic traces.…”
Section: Introductionmentioning
confidence: 99%
“…shale gas, tight gas and tight oil) has caused a significant interest in microseismic fracture monitoring [1,2]. Meanwhile, we are facing the enormous challenges of improving microseismic event locations and building accurate velocity model [3][4][5]. Various linear inversion techniques (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two types of sources are generally present in the hydraulic stimulation process. The first is generated by the perforation of the casing of the well (Warpinski et al, 2003) and presumably radiates most of its energy as a point force monopole. Second is the induced microseismicity which generally has a dominant double couple mechanism (Song et al, 2010;Song and Toksoz, 2011).…”
Section: Introductionmentioning
confidence: 99%